Antibacterial activity of soil-isolated Bacillus altitudinis/pumilus complex against methicillin-resistant Staphylococcus aureus from Mwanza, Tanzania - Reuben N. Abednego; Vitus Silago (AOSIS, 2023)
Antimicrobial resistance in methicillin-resistant Staphylococcus aureus and beta-lactamase-producing Gram-negative bacteria is a global health concern necessitating research and the development of effective antimicrobial agents. This study, conducted in May 2020 in Mwanza, Tanzania, aimed to determine the antibacterial activity of metabolites from soil-isolated Bacillus species against clinical bacterial pathogens. One soil-isolated Bacillus species, identified as Bacillus altitudinis/pumilus complex, showed antibacterial activity against Gram-positive cocci, including a methicillin-resistant S. aureus strain with inducible clindamycin resistance, previously isolated from a patient with osteomyelitis. Bacillus altitudinis/pumilus complex metabolites may be a potential source of antimicrobial agents against multidrug-resistant bacteria. What this study adds: The study supports existing research on the discovery and development of new antimicrobial agents against multi-drug-resistant bacteria. We report the antimicrobial activity of metabolites extracted from soil-isolated Bacillus altitudinis/pumilus complex strains against Gram-positive bacteria, including a methicillin-resistant Staphylococcus aureus strain with inducible clindamycin resistance